PEMANFAATAN DATA MODIS UNTUK IDENTIFIKASI DAERAH BEKAS TERBAKAR (BURNED AREA) BERDASARKAN PERUBAHAN NILAI NDVI DI PROVINSI KALIMANTAN TENGAH TAHUN 2009 - Suwarsono, Suwarsono; Yulianto, Fajar; Parwati, Parwati; Suprapto, Totok (Institut Teknologi Sepuluh Nopember, 2009)
Land and forest fire are the natural disasters that often occur in Indonesian regions, especially Sumatera and Kalimantan. The disasters cause deep impacts to environments and human beings, so it is necessary to conduct mitigation. The research area took place in Central Kalimantan Province. The objective of the research is to applicate the MODIS remote sensing imagery for supporting the land and forest fire mitigation efforts, that is identifying the burned area. The analyzing is done by using methods of NDVI changes before and after land and forest burned periods in 2009. The stages of the research consist of; fire hotspot frequency analyzing, NDVI changes calculation, threshold of NDVI changes establishing, and burned area estimation based on the threshold result. The results of the research show that the burned area in Central Kalimantan can be identified by using MODIS based on NDVI changes. The total numbers of burned area in 2009 are 122.900 hectares, most of them occurred in Pulangpisau, Kapuas, Katingan and Kotawaringin District. The results are needed to be verified in the next further research based on the field survey and or by using the high resolution imageries such as Landsat, SPOT-2 or 4, ALOS, Ikonos or Quickbird.